2021
DOI: 10.3389/fgene.2021.686298
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between the Characteristics of Alternative Splicing Events, Prognosis, and the Immune Microenvironment in Breast Cancer

Abstract: ObjectiveAlternative splicing (AS) is the mechanism by which a few genes encode numerous proteins, and it redefines the concept of gene expression regulation. Recent studies showed that dysregulation of AS was an important cause of tumorigenesis and microenvironment formation. Therefore, we performed a systematic analysis to examine the role of AS in breast cancer (Breast Cancer, BrCa) progression.MethodsThe present study included 993 BrCa patients from The Cancer Genome Atlas (TCGA) database in the genome-wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…9) indicates that three of them have been found associated with breast cancer, including, RPS21, PPP1CA and TXNIP. RPS21 ’s role in breast cancer is not clear now, but one transcript of RPS, AA-RPS21 , is differentially expressed in cancerous tissues, indicating its potential driver role in breast cancer [34]. PPP1CA together with PRKACG and PRKAR1B were found to be the most strongly associated with breast cancer–specific survival [35].…”
Section: Resultsmentioning
confidence: 99%
“…9) indicates that three of them have been found associated with breast cancer, including, RPS21, PPP1CA and TXNIP. RPS21 ’s role in breast cancer is not clear now, but one transcript of RPS, AA-RPS21 , is differentially expressed in cancerous tissues, indicating its potential driver role in breast cancer [34]. PPP1CA together with PRKACG and PRKAR1B were found to be the most strongly associated with breast cancer–specific survival [35].…”
Section: Resultsmentioning
confidence: 99%
“…The potential to use cancer-specific AS events as biomarkers for prognosis and treatment targets is gaining recognition (36,37). Recent studies have focused on exploring the prognostic value of AS events in malignancies such as colorectal cancer (38), breast cancer (39), hepatocellular carcinoma (40), and kidney cancer (41). LUAD is an aggressive tumor with increasing incidence and poor outcomes (42), and thus, the identification of biomarkers for diagnosis and therapy is urgently required.…”
Section: Discussionmentioning
confidence: 99%
“…The dysregulation of an immune response is associated with oncogenesis [ 14 , 15 ]. Studies have indicated the implication of alternative splicing in immune dysregulation [ 16 ] and also the presence of abnormal isoforms and their aberrant expression levels as cancer hallmarks [ 17 ]. This review unmasks the complexity of immunomodulatory genes splicing dysregulation in carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%